Pengembangan Modul Administrasi Perkantoran pada Mata Pelajaran Administrasi Humas dan Keprotokolan Kelas XI APK di SMK Muhammadiyah 1 Lamongan - Siska Yustina Purnama; Siti Sri Wulandari (Universitas Negeri Surabaya, 2021)
The purpose a research to develop teaching materials in the form of Public Relations and Protocol Administration module-based curriculum Odd Semester 2013 for Class XI APK. The purpose of this development research is to describe the process of developing public relations and protocol administration modules, analyzing the feasibility of public relations and protocol administration modules, and analyzing the responses of class XI APK students to the public and protocol administration modules. This study uses a 4D development model, which consists of the define,design, develop, and disseminate.The population of this research is the XI APK grade students at SMK Muhammadiyah 1 Lamongan. The sample of this study was only 20 students from a total of 28 students, because they used a small group. Data collection techniques in this study used the material expert validation sheet, the language expert validation sheet, the graphic expert validation sheet, and the student response questionnaire sheet. Data analysis techniques used in this study were module validation analysis and student response questionnaire analysis. The results of the research on the development of public relations and protocol administration modules obtained a percentage of eligibility of 85% with a very appropriate interpretation and the results of a limited trial aimed at 20 students of the public relations and protocol administration module obtained a 81% eligibility percentage with a very appropriate interpretation. Then, it can be concluded if the Public Relations and Protocol Administration Module Class XI APK can be declared feasible to be used as teaching material in learning.